Діагностичне та прогностичне значення молекулярно-біохімічних маркерів у пацієнтів із захворюваннями тканин пародонту та дефектами зубних рядів - Романюк, Віктор Миколайович; Возний, Олександр Вікторович; Павлов, Сергій Васильович; Романюк, В. М.; Возный, А. В.; Павлов, С. В.; Romaniuk, V. M.; Vozniy, O. V.; Pavlov, S. V. (Українська медична стоматологічна академія, 2020)
Резюме. Хронічний генералізований пародонтит одне з найпоширеніших хронічних захворювань у світі. Аналіз літературних джерел показав значну патогенетичну роль деяких інтермедіаторів метаболізму кісткової тканини, прозапальних пептидів: матриксних металлопротеїназ, лактоферину та кателіцидину у розвитку захворювань тканин пародонту. Метою дослідження було встановити прогностично вагомі молекулярно-біохімічні критерії при плануванні комплексного лікування пацієнтів із захворюваннями тканин пародонту та дефектами зубних рядів. Обстежено 80 пацієнтів віком від 18 до 65 років. Серед них 20 здорових пацієнтів склали контрольну групу та 60 основну із захворюваннями тканин пародонту та дефектами зубних рядів. Вивчення стану гігієни порожнини рота за допомогою індексу Грін-Верміліона (OHI-S) показав, що у хворих на ХГП І ст. тяжкості перевищувало норму у 2 рази, при ХГП ІІ та ІІІ ст. тяжкості перевищувало норму у 3 та 4 рази відповідно. Значення індексу РМА у пацієнтів з ХГП І ст. тяжкості – 54%, що перевищувало у 6 разів показники контрольної групи. У пацієнтів з ХГП ІІ ст. PMA- 66%, у пацієнтів з ХГП ІІІ ст. – 81%. Індекс SBI у пацієнтів з І ст. тяжкості ХГП склав 13%, у пацієнтів з ХГП ІІ ст. тяжкості -35%, у пацієнтів з ХГП ІІІ ст. – 69%. ММР-8 в ротовій рідині підвищувався в прямій залежності від ступеню тяжкості пародонтиту. При І ступеню важкості пародонтиту показники ММР-8 – 0,47±0,08 ng/ml. Показники при ІІ та ІІІ ступеню важкості збільшувались в 4 та 7 разів відповідно. LL-37 визначався в зворотній залежності від ММР-8, тобто зменшувались відповідно тяжкості пародонтиту. При І ступеню важкості пародонтиту показники LL37 – 3,77±0,10 ng/ml. Показники при ІІ та ІІІ ступеню важкості зменшувались в 5 та 12 разів відповідно. При І ступеню важкості пародонтиту показники Lf – 44,02±2,60 ng/ml. Показники при ІІ та ІІІ ступеню важкості збільшувались в 5 та 8 разів відповідно. Визначення рівня біологічних маркерів ротової рідини являється перспективним діагностичним методом, не потребує спеціальної підготовки від лікаря-стоматолога, є малоінвазивною методикою, та дозволяє оцінити саме поточний стан тканин протезного ложа. Резюме. Хронический генерализованный пародонтит одно из самых распространенных хронических заболеваний в мире. Анализ литературных источников показал значительную патогенетическую роль некоторых интермедиаторов метаболизма костной ткани, провоспалительных пептидов: матриксных металлопротеиназ, лактоферрина и кателицидина в развитии заболеваний тканей пародонта. Целью исследования было установить прогностически значимые молекулярно-биохимические критерии при планировании комплексного лечения пациентов с заболеваниями тканей пародонта и дефектами зубных рядов. Обследовано 80 пациентов в возрасте от 18 до 65 лет. Среди них 20 здоровых пациентов составили контрольную группу и 60 основную с заболеваниями тканей пародонта и дефектами зубных рядов. Изучение состояния гигиены полости рта с помощью индекса Грин-Вермилион (OHI-S) показал, что у больных ХГП I в. тяжести превышало норму в 2 раза, при ХГП II и III ст. тяжести превышало норму в 3 и 4 раза соответственно. Значение индекса РМА у пациентов с ХГП I в. тяжести – 54%, что превышало в 6 раз показатели контрольной группы. У пациентов с ХГП II в. PMA – 66%, у пациентов с ХГП ІІІ ст. – 81%. Индекс SBI у пациентов с I ст. тяжести ХГП составил 13%, у пациентов с ХГП II ст. тяжести – 35%, у пациентов с ХГП III ст. – 69%. ММР-8 в ротовой жидкости повышался в прямой зависимости от степени тяжести пародонтита. При I степени тяжести пародонтита показатели ММР-8 – 0,47±0,08 ng/ml. Показатели при II и III степени тяжести увеличивались в 4 и 7 раз соответственно. LL-37 определялся в обратной зависимости от ММР-8, то есть уменьшался соответственно тяжести пародонтита. При I степени тяжести пародонтита показатели LL37 – 3,77±0,10 ng/ml. Показатели при II и III степени тяжести уменьшались в 5 и 12 раз соответственно. При I степени тяжести пародонтита показатели Lf – 44,02±2,60 ng/ml. Показатели при II и III степени тяжести увеличивались в 5 и 8 раз соответственно. Определение уровня биологических маркеров в ротовой жидкости является перспективным диагностическим методом, не требует специальной подготовки от врача-стоматолога, является малоинвазивной методикой, и позволяет оценить именно текущее состояние тканей протезного ложа. Abstract. Chronic generalized periodontitis is one of the most common chronic diseases in the world. Periodontal diseases include a wide range of inflammatory reactions that affect the retaining structures of the teeth, which ultimately leads to their loss. With the help of various laboratory methods of studying the composition of oral fluid, it is possible to determine the activity of substances involved in cellular metabolism in inflammatory diseases of the oral cavity. The study of medical literature has confirmed considerable pathogenic role of some biomolecules, namely of matrix metalloproteinases of lactoferrin and cathelicidin, in the development of periodontium tissue diseases. It is these molecular markers that are given considerable attention in the development of protocols for laboratory screening of oral diseases. The purpose of the present research was to estimate prognostically valid criteria at planning implantological and prosthetic treatment of patients with periodontium tissues disorders and defects of dental arches. 80 patients aged 18 to 65 years were selected for the present study. Among them, 20 healthy patients comprised observational group, and 60 patients with periodontium tissues diseases formed treatment group. There were 19 patients with first-degree periodontitis, 27 patients with second-degree periodontitis and 14 patients with thirddegree periodontitis and defects of dental arches. The study of oral hygiene using the Green Vermilion Index (OHI-S) showed that in patients with first-degree periodontitis exceeded the norm by 2 times, with second and third-degree periodontitis exceeded the norm by 3 and 4 times, respectively. The value of the PMA index in patients with first-degree periodontitis was 54%, which is 6 times higher than in the control group. In patients with second-degree periodontitis, this figure was 66% in patients with third-degree periodontitis – 81%. SBI in patients with first-degree periodontitis value averaged 13%, in patients with second-degree periodontitis, this figure was 35%, in patients with third-degree periodontitis – 69%. Level of MMP-8 in oral cavity fluid increased directly depending on periodontitis degree. At first-degree periodontitis, values of MMP-8 increased 3 times in comparison with the observation group (0,47±0,08 ng/ml). Values at second- and third-degree periodontitis increased 4 and 7 times correspondingly. The increase of MMP-8 level in the oral cavity indicates the destruction of connective tissue that points at the intensity of inflammation processes of oral cavity mucous membranes and at the necessity in periodontological treatment. Values of LL-37 were estimated in inversed relation to MMP-8, i.e. they decreased according to periodontitis degree. At first-degree periodontitis, values of cathelicidin decreased 2 times in comparison with the observation group (3,77±0,10 ng/ml). Values at second- and third-degree periodontitis decreased 5 and 12 times correspondingly. Received findings demonstrate the decrease of antimicrobial activity both against Gram-positive and against Gram-negative bacteria. The deficiency of LL-37 in the oral fluid points at the direction of pathological manifestations and reflects the level of periodontium tissues inflammation. Values of Lactoferrin increased directly depending on periodontitis degree. At first-degree periodontitis, values of lactoferrin increased 2 times in comparison with the observation group (44,02±2,60 ng/ml). Values at second- and third-degree periodontitis increase 5 and 8 times correspondingly. These findings prove the decrease of tissue immunity in the oral cavity. It was discovered that values of lactoferrin and MMP-8 demonstrate direct correlational dependence which indicates the activity of inflammation processes in periodontium tissues. Values of lactoferrin and cathelicidin demonstrate inversed correlational dependence. Estimation of level of biomarkers in oral cavity fluid is a prospective diagnostic method which is minimally invasive, does not require specific qualification of a dentist, and gives an opportunity to estimate the present state of denture base tissues, which allows rational planning of prosthetic rehabilitation of dental patients and controlling the process of adaptation.
Диагностическое и прогностическое значение молекулярно-биохимических маркеров у пациентов с заболеваниями тканей пародонта и дефектами зубных рядов
Diagnostic and prognostic value of molecular biochemical markers in patients with periodontal tissue disorders and dental defects
Keywords: біологічні маркери; захворювання тканин пародонту; діагностика; биологические маркеры; заболевания тканей пародонта; диагностика; biological markers; periodontal diseases; diagnosis